Spatial footprints of context-aware digital services. Eventual self-regulated alignments of dating apps with the urban shape. - Lorente-Riverola, Iñigo; Ruiz-Sánchez, Javier (Springer, 2018)
Since the 'smartphone' outbreak in 2007, the unprecedented growth of context-aware services - so called 'hyperlocal' or Location-Based Services (LBS) - on top of the preexisting urban systems are transforming the way that citizens communicate. As a consequence, new self-regulated cellular digital networks are emerging. Their collective use is transforming the mobility patterns and uses of the urban public and private spaces without subsuming or replacing them. The characteristics and implications for the planning of this new 'digitally integrated urban space' (Ratti and Claudel in The City of Tomorrow: Sensors, Networks, Hackers, and the Future of Urban Life. Yale University Press, 2016) have to be addressed. This paper focuses on the behavioral/eventual changes at the hybrid digital and physical space. The goal is to analyze how the shape and structure of a LBS changes given an external disruption and how does it adapt to new scenarios, proving both the existence and resiliency of the digital urban space. The method applies Python scripting and GIS techniques to represent live and anonymized data from popular dating services during the Madrid Gay Pride week, including the days before the Parade to establish comparisons between the usual and the occasional scenarios. This comparison enables us to extract conclusions about how the spatial shape of the services can change; which physical limits are dissolved by the digital network's topology; and how stabile the network behaves comparing the usual mobility patterns of its users with the occasional ones.
Keywords: Kommunikation; Digitalisierung; Applikation; GIS; Mobilitätsverhalten; Stadtraum